Molecular docking analysis of Carica papaya Linn constituents as antiviral agent - Narayanaswamy, Radhakrishnan; Lam, Kok Wai; Mohd Esa, Norhaizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Carica papaya (papaya) fruits are available throughout the world and it is well accepted as food or as a quasi-drug. Aqueous papaya leaves extract have been used as treatment for dengue fever. This prompted us to carry out the docking study on these nine selected ligands (phyto-constituents of papaya) which are carpaine, dehydrocarpaine I and II, cardenolide, p-coumaric acid, chlorogenic acid, caricaxanthin, violaxanthin and zeaxanthin. These phyto-constituents were evaluated on the docking behaviour of dengue serotype 3 RNA-dependent RNA polymerase (RdRp); influenza A (H1N9) virus neuraminidase (NA); chikungunya virus glycoprotein (E3-E2-E1) and chikungunya virus non-structural protein2 (nsP2) protease using Discovery Studio Version 3.1. In addition, molecular physicochemical, drug-likeness, ADMET (Absorption, Distribution, Metabolism, Excretion and Toxicity) and TOPKAT (Toxicity Prediction by Komputer Assisted Technology) analyses were done. The molecular physicochemical analysis revealed that cardenolide and p-coumaric acid (2 ligands) complied with Lipinski’s rule of five. Dehydrocarpaine II, cardenolide, caricaxanthin, violaxanthin and zeaxanthin all the five ligands were predicted to have plasma protein binding (PPB) effect. Docking studies and binding free energy calculations revealed that p-coumaric acid exhibited very least binding energy irrespective of its target protein. Hence, the results of this present study exhibited the potential of these nine ligands as antiviral agent.